Futures Study of Smart Contracts in the Banking Industry - Mohebi Ashtiani, Saeed; Adeli, Omid Ali; Pourfakharan, Mohammadreza; Maleki, Mohammad Hasan (Management Strategies and Engineering Sciences, 2024)
Smart contracts are one of the most significant applications of blockchain technology, which have gained considerable importance in the financial industry. These contracts promote transparency and enhance good governance in the banking sector. The present research aims to conduct a Futures Study of smart contracts in the banking industry using a scenario-building approach. This research is applied in nature, and methodologically, it is a mixed-methods study. In this research, fuzzy Delphi, fuzzy WASPAS, and interviews with focus groups were used to analyze the data. In the first step, 37 drivers were identified through a literature review and interviews with blockchain experts. These drivers were then filtered using expert questionnaires and the fuzzy Delphi method. Nine drivers were selected for final prioritization using the fuzzy WASPAS method. The filtered drivers were ranked through prioritization questionnaires and the fuzzy WASPAS method. Based on the scores of the fuzzy WASPAS method and considering three criteria—expertise, importance intensity, and certainty level—the drivers of coordination and integration level of banks in adopting new technologies and contracts, as well as the integration level of information systems in the banking industry, were given the highest priority and were selected for scenario mapping. The research scenarios were developed based on the two prioritized drivers and through interviews with focus groups. These scenarios included: Smart Banking, Integrated Banking, Island Banking, and Traditional Banking. Smart Banking represents the ideal scenario, and practical recommendations were developed based on this scenario.